Deglutition-Induced Atrial Tachycardia - Farah, Nesrine; Trana, Catalina (Curēus (Palo Alto, CA), 2021)
While bradyarrhythmia is the most common arrhythmia during deglutition, tachycardias are considered to be a very rare condition with approximately 50 cases documented worldwide. The subjects are usually men with no structural heart disease or gastrointestinal pathology, and symptoms may vary from palpitations to lightheadedness or syncope.Management is based on adapting alimentary habits in combination with agents such as beta-blockers, calcium channel blockers, and class IA, IC, and III drugs. Radiofrequency catheter ablation offers a permanent cure in the majority of the reported cases.We report the case of a 51-year-old male with swallowing-induced palpitations, corresponding to brief episodes of atrial tachycardia. Beta-blockers and calcium channel blockers were interrupted because of intolerance. Lifestyle measures with fractionated meals allowing small boluses significantly reduced symptoms. The patient was reticent to invasive measures.